Morphological and Anatomical Features of the Structure of Vegetative and Generative Organs of Lycium Chinense Mill. and Lycium Barbarum L. Solanaceae Juss. in the Conditions of Uzbekistan - Alikarieva, Durdona Mirmakhmudovna (RA Journal of Applied Research, 2022)
The characteristics of Lycium chinense Mill and Lycium barbarum L., species, taxonomy, origin and use in medicineare given. The adaptation of these plants in the conditions of the Botanical Garden of Tashkent, as well as in the conditions of the Namangan region, was studied. The morphological and anatomical structures of two species of the genus Lycium have been studied. The morphology and structure of vegetative and generative organs, which differ from each other in leaf shape and venation, are described. Leaf cells are studied in detail: the epidermis of the upper side has a smaller number of stomata, which makes it possible to reduce the evaporation of water in summer drought conditions. The spongy parenchyma is chlorophyllon-bearing. Calcium oxalate was found in palisade and spongy parenchyma cells. Conductive bundles of bicollateral type are numerous, consist of phloem and xylem. The center of the petiole has one vascular bundle with a closed bicollateral type. Parenchymal cells are thin-walled, but some have hydrocytic cells. The petiole of the leaf in a transverse section is of the parenchymal-fascicular type, has numerous parenchymas and vascular bundles. Collenchyma is located under the epidermis, based on osmotic phenomena. The stems are sclerified, helping to resist various environmental influences. It was found that with age, the cambium changes the anatomical structure of the stem, and also annually produces secondary xylem.The fruit of Lyciumchinense is a berry, syncarpous and 2-celled. Nucleoli were found in the epidermis. On a transverse section, the pericarp consists of several parenchymal cells, the walls of the epidermis are thickened and cutinized. The mesocarp consists of multi-row parenchymal cells. They are tangentially elongated in the outer layers, and rounded in the inner ones. Endocarp of irregular shape. The seeds of Lyciumchinense are large, round, and have a beak-shaped rib. The cells of the outer epidermis become lignified over time. The parenchyma of the intigument is enclosed between the epidermis. The perisperm is absent. The endosperm is of a cellular type, the endosperm cells contain oil droplets and aleurone grains. Based on the results, morphological-anatomical-histological features were determined. The data obtained can serve to identify plant materials, in environmental studies, as well as to determine diagnostic features.